2020
DOI: 10.1371/journal.ppat.1008386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of P[II] major human rotavirus VP8* domain recognition of histo-blood group antigens

Abstract: Initial cell attachment of rotavirus (RV) to specific cell surface glycan receptors, which is the essential first step in RV infection, is mediated by the VP8* domain of the spike protein VP4. Recently, human histo-blood group antigens (HBGAs) have been identified as receptors or attachment factors for human RV strains. RV strains in the P[4] and P[8] genotypes of the P [II] genogroup share common recognition of the Lewis b (Le b) and H type 1 antigens, however, the molecular basis of receptor recognition by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 84 publications
(260 reference statements)
2
36
0
Order By: Relevance
“…Interestingly, a trisaccharide glycan Galα1-3Galβ1-4Glc (glycan number 117) containing an αGal was found to be recognised by multiple strains representing one RVC and six RVA genotypes, indicating evolutionary connections among these genotypes with the αGal glycan as a common receptor (Figure 1). Four strains exhibited strongest binding signals to the αGal containing glycans, including two murine RVAs in the P [16] genotype (the prototype murine RV EDIM and a variant murine RV EMcN [22,23]), P [3] genotype in RVA that infects animals and humans, and a bovine strain in a RVC genotype. It is known that the αGal transferase responsible for synthesis of αGal glycan is produced in some animal species, but the gene encoding the specific αGal transferase is inactive in humans [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, a trisaccharide glycan Galα1-3Galβ1-4Glc (glycan number 117) containing an αGal was found to be recognised by multiple strains representing one RVC and six RVA genotypes, indicating evolutionary connections among these genotypes with the αGal glycan as a common receptor (Figure 1). Four strains exhibited strongest binding signals to the αGal containing glycans, including two murine RVAs in the P [16] genotype (the prototype murine RV EDIM and a variant murine RV EMcN [22,23]), P [3] genotype in RVA that infects animals and humans, and a bovine strain in a RVC genotype. It is known that the αGal transferase responsible for synthesis of αGal glycan is produced in some animal species, but the gene encoding the specific αGal transferase is inactive in humans [24].…”
Section: Resultsmentioning
confidence: 99%
“…RVAs representing two P[I] genotypes (P [3] and P [7]) known as sialic acid (SA)-dependent and another two P[I] genotypes known as SA-independent (P [15] and P [23]) [7,25,26] have been found binding SA-glycans at high affinity ( Figure 2). Interestingly, these four SA-binding genotypes are genetically closely related and form a cluster together with other four SA-dependent genotypes (P [1], P [2], P [16] and P [20], excepting P [18], Figure 1 and Table 1) in the RVA P[I] genogroup. These findings indicated a new direction of RV evolution under selection of SA-containing glycans, consistent with the previous finding that many animal RVAs are SA-dependent [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recent structural studies involving P[8] VP8* binding to HBGA presented conflicting results. While some indicate the additional fucose conferred by the Lewis b antigen would cause steric hindrance to the interaction, other studies demonstrated binding of P[8] VP8* to the Lewis b antigen via a pocket formed by two β-sheets [ 63 , 64 , 65 ]. Further studies are warranted to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%